European intensive care nurses' cultural competency: An international cross-sectional survey - Dobrowolska, Beata; Gutysz-Wojnicka, Aleksandra; Ozga, Dorota; Barkestad, Eva; Benbenishty, Julie; Breznik, Kristijan; Filej, Bojana; Jarosova, Darja; Kaučič, Boris Miha; Nytra, Ivana; Smrke, Barbara; Zelenikova, Renata; et al. (Intensive & critical care nursing, 2020)
OBJECTIVES: To determine the level of cultural competence of European critical care nurses. DESIGN: A multi-country survey performed in 2017 as a part of the European project Multicultural Care in European Intensive Care Units. METHOD: Online survey of critical care nurses in 15 European countries (n = 591) using the Healthcare Provider Cultural Competence Instrument consisting of 49 items divided into five subscales: awareness and sensitivity, behaviour, patient-centred orientation, practice orientation and self-assessment. Descriptive and correlational analyses were performed. RESULTS: Critical care nurses scored highest for 'awareness and sensitivity' (M = 5.09, SD = 0.76), and lowest for 'patient-centred communication' (M = 3.26, SD = 0.94). Nurses from northern and southern Europe scored higher across all subsets of the cultural competence instrument (all subsets, p < 0.001) than nurses from central Europe. Speaking other languages significantly correlated with higher scores in all subscales (all > 0.05) except 'practice orientation'. Previous education on multicultural nursing significantly correlated with higher scores in all subscales (all > 0.01) except patient-centred communication; and visits to other countries was negatively correlated with all subscales (all, p > 0.001) except patient-centred communication. CONCLUSION: Being exposed to cultural diversity in different ways, like living in a multicultural country, speaking a second language and visiting other countries may influence development of cultural competence. Therefore, programmes which facilitate multicultural clinical practice are strongly recommended in nursing education.
Keywords: Cross-Sectional Studies; Cultural competency; Male; Europe; Evropa; Middle Aged; průzkumy a dotazníky; Cultural Competency; mužské pohlaví; průřezové studie; Adult; kulturní kompetence; zdravotní sestry; internacionalita; ženské pohlaví; Critical care nurses; Humans; Surveys and Questionnaires; lidé středního věku; Cross-sectional survey; dospělí; Female; Nurses; Critical Care Nursing; ošetřovatelská péče o pacienty v kritickém stavu; lidé; Internationality